Culicidae (Diptera, Culicomorpha) from the western Brazilian Amazon: Juami-Japurá Ecological Station - Hutchings, Rosa Sá Gomes; Hutchings, Roger William; Sallum, Maria Anice Mubeb (Revista Brasileira de Entomologia, 2010)
With 312 trap-hours of sampling effort, 1554 specimens of Culicidae (Diptera) were collected, using CDC and Malaise traps, in nine different locations along the Juami River, within the Juami-Japurá Ecological Station, Amazonas State, Brazil. A list of mosquito species with 54 taxa is presented, which includes three new distributional records for the state of Amazonas. The species found belong to the genera Anopheles, Aedeomyia, Aedes, Psorophora, Culex, Coquillettidia, Sabethes, Wyeomyia and Uranotaenia.
Culicidae (Diptera, Culicomorpha) da Amazônia Ocidental Brasileira: Estação Ecológica Juami-Japurá
Keywords: Aedeomyia; Coquillettidia; Culicidae; Culicomorpha; Diptera; Psorophora; Sabethes; Wyeomyia